Decreased Insulin Sensitivity in Telomerase-Immortalized Mesenchymal Stem Cells Affects Efficacy and Outcome of Adipogenic Differentiation in vitro - Kulebyakin, Konstantin; Tyurin-Kuzmin, Pyotr; Efimenko, Anastasia; Voloshin, Nikita; Kartoshkin, Anton; Karagyaur, Maxim; Grigorieva, Olga; Novoseletskaya, Ekaterina; Sysoeva, Veronika; Makarevich, Pavel; Tkachuk, Vsevolod (Frontiers in Cell and Developmental Biology, 2021)
Modern biomedical science still experiences a significant need for easy and reliable sources of human cells. They are used in the investigation of pathological processes underlying disease, for pharmacological studies, and eventually as a therapeutic product in regenerative medicine. For decades adult pool of mesenchymal stem / stromal cells (MSCs) remains a promising source of stem and progenitor cells. Their isolation is more feasible compared to most other stem cells from human donors yet they do have a fair share of disadvantages. The latter includes significant variability between donors, loss of potency, and transformation during long-term culture which may impact efficacy and reproducibility of research. One possible solution is a derivation of immortalized MSCs lines which receive a wider use in many medical and biological studies. In the present work, we demonstrated that in the most widely commercially available hTERT-immortalized MSCs cell line ASC52telo, sensitivity to hormonal stimuli was reduced which affected their differentiation efficacy. We found that immortalized MSCs have impaired insulin-dependent and cAMP-dependent signaling which reduced their adipogenic, but not osteogenic or chondrogenic potential in experimental conditions. Our findings indicate that hTERT-immortalized MSCs may present a suboptimal choice for studies involving hormonal sensitivity.